1995
DOI: 10.1051/lait:1995643
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological changes throughout the manufacturing and ripening of a Spanish goat's raw milk cheese (Armada variety)

Abstract: Summary -The microbial groups of technological interest (aerobic mesophilic flora, presumptive lactococci, presumptive lactobacilli, presumptive leuconostocs, presumptive enterococci, presumptive Micrococcaceae and mou Ids and yeasts) were enumerated throughout the ripening process in 4 batches of Armada goat's milk cheese (2 ripened in summer and 2 ripened in autumn). High counts of ail microbial groups were observed in milk (loglO cfu/g: aerobic mesophilic flora 6. presumptive enterococci 2.9~.29,; the high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
48
2
4

Year Published

2001
2001
2015
2015

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(62 citation statements)
references
References 24 publications
8
48
2
4
Order By: Relevance
“…With respect to the NaCl content, the levels increased gradually to 2.5% by 60 d. Values were also very close to those that have been reported for some other goat's milk cheeses [21,24,33], although usually goat's milk cheeses have high salt levels [16,18,36]. Surprisingly, the present salt content in Ibores cheese is almost 50% 582 M. Mas et al lower than that observed a decade ago for the same type of cheese.…”
Section: Physicochemical Changes During Ripeningsupporting
confidence: 88%
See 4 more Smart Citations
“…With respect to the NaCl content, the levels increased gradually to 2.5% by 60 d. Values were also very close to those that have been reported for some other goat's milk cheeses [21,24,33], although usually goat's milk cheeses have high salt levels [16,18,36]. Surprisingly, the present salt content in Ibores cheese is almost 50% 582 M. Mas et al lower than that observed a decade ago for the same type of cheese.…”
Section: Physicochemical Changes During Ripeningsupporting
confidence: 88%
“…lactis ssp. lactis as almost the sole representative of the genus Lactococcus is reported frequently for raw milk cheeses [18,19,22,30,33]. It is also in agreement with the observations of Weerkamp et al [35] on the predominance of Lc.…”
supporting
confidence: 91%
See 3 more Smart Citations